Protection against clinical malaria by heterologous immunoglobulin G antibodies against malaria-infected erythrocyte variant surface antigens requires interaction with asymptomatic infections. - Kinyanjui, S; Mwangi, T; Bull, P; Newbold, C; Marsh, K (2004)
Erythrocytes infected with mature stages of Plasmodium falciparum express variant surface antigens (VSAs) of parasite origin, including P. falciparum erythrocyte membrane protein 1. Anti-VSA antibodies protect against clinical malaria caused by parasites bearing VSAs to which they are specific (homologous), but their role in protecting against heterologous infection is unclear. Here, we report that, among 256 Kenyan children involved in a 1-year active case surveillance study, asymptomatic parasitemia was associated with an enlarged repertoire of anti-VSA immunoglobulin G (IgG) antibodies specific to apparently heterologous parasite isolates, as measured by flow cytometry. Together, asymptomatic infection and anti-VSA IgG were associated with reduced odds of experiencing an episode of clinical malaria during follow-up, whereas, independently, they were associated with increased susceptibility. These results support previous findings and underline the importance of considering the parasitological status of study participants when examining the role that immune responses to VSAs and other malaria antigens play.